An AceDAN–porphyrin(Zn) dyad for fluorescence imaging and photodynamic therapy via two-photon excited FRET. Issue 12 (23rd October 2018) - Zhu, Mengliang; Su, Chaorui; Xing, Peipei; Zhou, Yabin; Gong, Lei; Zhang, Jinghui; Du, Hongwu; Bian, Yongzhong; Jiang, Jianzhuang
Abstract : A FRET based AceDAN–porphyrin(Zn) dyad was designed to generate red emission and singlet oxygen ( 1 O2 ) simultaneously, which were utilized successfully for two-photon excited fluorescence imaging and PDT of cancer cells. Abstract : The recent development of the two-photon technique offers a unique opportunity to improve the depth of imaging and treatment in photodynamic therapy (PDT). Herein, we designed a fluorescence resonance energy transfer (FRET) based AceDAN–porphyrin(Zn) dyad for two-photon excited fluorescence imaging and PDT of cancer cells simultaneously, in which the AceDAN moiety was selected as the two-photon absorption donor and the porphyrin(Zn) moiety served as the energy acceptor. Upon one-photon or two-photon excitation, the excited state energy of the AceDAN donor was transferred to the porphyrin(Zn) acceptor with high efficiency ( η EET = 98%), where red fluorescence and singlet oxygen were generated. Dyad1 exhibited high photocytotoxicity towards A549 cells (IC50 = 4.3 μM) with rapid cellular uptake while displaying low dark-cytotoxicity. Furthermore, by combining the advantages of two-photon excitation with a porphyrin(Zn) photosensitizer, the AceDAN–porphyrin(Zn) dyad has been successfully applied to A549 cells for imaging and photodynamic therapy under two-photon laser irradiation.